Cost of Pulmonary Arterial Hypertension in Peru: Costo de la hipertensión arterial pulmonar en el Perú - Hernández, Fabian (2021)
Introduction: Pulmonary arterial hypertension (PAH) is a low prevalence condition for which there is very little information in Peru. Several studies indicate that it is associated with elevated costs for health systems in the world. Objective: To establish the economic burden of PAH in the Peruvian context. Methods: Information on the use of health resources was collected through consultations with clinical experts and key opinion leaders. Cost data was obtained from two tariff manuals and from the Observatory of Pharmaceutical Products (DIGEMID). Results: Expert consultations indicated that about 68% of the patients were in an intermediate stage of the disease and that the use of sequential combination therapy is predominant in FC III and FC IV stages, compared to earlier stages. The annual cost of PAH treatment in Peru was $ 14,842 USD, where the main cost driver was drugs (81.72%), followed by diagnosis (8.96%) and outpatient follow-up (5.75%). Conclusions: Information on pulmonary arterial hypertension in Peru is critical for decision makers, due to the high economic impact that the disease entails. Moreover, studies in this therapeutic area are relevant for the dissemination of knowledge of the disease to different health professionals.